Jurisdição tributária e controle da coisa julgada contrária a precedentes: ascensão de uma lógica instrumental - Massud, Rodrigo Giacomeli Nunes (2024)
This thesis intends to provide an unprecedented methodological systematization to the study of res judicata and its means of confrontation in the face of contrary precedents in tax matters. To this end, we take as a critical reference the judgment with general repercussion of Themes 881 and 885 by the Federal Supreme Court, forming a historical landmark that ended up establishing a new paradigm in national tax litigation. Thus, from a new perspective of tax legality as equality, we seek to systematize the legal bases capable of providing legal certainty in the confrontation of res judicata held by taxpayers, reconciling stability, adaptation and motion (the maxim of pragmatism), especially taking into account the rise of two modern epistemological vectors: instrumentalism and consensualism